2023
DOI: 10.1186/s13046-023-02727-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological roles of A-to-I editing: implications in innate immunity, cell death, and cancer immunotherapy

Abstract: Adenosine-to-inosine (A-to-I) editing, a key RNA modification widely found in eukaryotes, is catalyzed by adenosine deaminases acting on RNA (ADARs). Such RNA editing destabilizes endogenous dsRNAs, which are subsequently recognized by the sensors of innate immune and other proteins as autologous dsRNAs. This prevents the activation of innate immunity and type I interferon-mediated responses, thereby reducing the downstream cell death induced by the activation of the innate immune sensing system. ADARs-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Furthermore, over 20% of the inosine edits located in 3’UTRs overlap potential microRNA binding sites (Table S9). As inosine has different base-pairing properties than adenosine 46 , these changes may alter the efficiency of microRNA targeting and regulation of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, over 20% of the inosine edits located in 3’UTRs overlap potential microRNA binding sites (Table S9). As inosine has different base-pairing properties than adenosine 46 , these changes may alter the efficiency of microRNA targeting and regulation of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic inflammatory circumstances increase RNA editing, which stabilizes proinflammatory transcripts and puts “fuel on the fire” for the ongoing inflammatory response. 55 Despite its potential impact on disease progression, the role of RNA editing in the host during an infection needs deeper investigation in different disease contexts. Recent studies on SARS-CoV-2 infection-mediated editing of host RNA have presented conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK3, a member of the receptor interacting protein kinase family, interacts with RIPK1 to form necroptotic complexes, activating MLKL and initiating necroptosis, thereby repressing cancer development [ 36 , 53 ]. In addition, it has been found that RIPK3 can interact with ZBP1 receptor to mediate necroptosis and PANoptosis [ 54 ].…”
Section: Crosstalk Between Apoptosis Pyroptosis and Necroptosismentioning
confidence: 99%